(3CNdGbjGJ GdCYeGd GdGOGQjI h GdGbJUGOjI aj YGde eJZjQ (B/s - (3MHjH, cejds; (3HhdS, LGf s ((3dHfGf(B: s (3GdeDSSI GdMOjKI ddcJGH(B, s, 2010)
(3GdJWhQ GdacQj deHOC GdGNdGbjGJ aj GdGYeGd , Gdbje GdCNdGbjI aj GdYed, GdGOGQI GdGNdGbjI h GdGNdGbjGJ aj GdGOGQI GdYGeI , eHGOF CNdGbjI aj CYeGd GdTQcI h GdeDSSI, GdGNdGbjGJ aj GdYed GdSjGSj, GdTaGajI h GdeSGAdI, GdMOGKI h GdGNdGbjGJ aj GdGYeGd, CNdGbjGJ GdJShjb, GdNUNUI h GdGLQGAGJ GdCNdGbjI aj GdCYeGd, CNdGbjGJ GdYed GdGYdGej, GdYhdeI HCHYGOgG GdGbJUGOjI h GdSjGSjI h GdKbGajI, GdYhdeI h GdGNdGbjGJ aj GdGYeGds
(3edGMb U(B.253 (3HHdjhZQGajG(B: (3U(B.280-282s
Keywords: (3EOGQI GdCYeGds; (3GdCNdGb GdegfjIs